"Stop Calling Me a Youth!": Understanding and Analysing Heterogeneity Among Ugandan Youth Agripreneurs. Issue 2 (August 2022) - Turolla, Maya; Swedlund, Haley J.; Schut, Marc; Muchunguzi, Perez
The African "youth" population is growing at a fast and steady pace, attracting attention from scholars, policymakers, and politicians. Yet, we know relatively little about this large and heterogeneous segment of the population. This paper presents data from 110 interviews and ten focus groups with youth engaged in commercial agriculture across all four regions of Uganda. Capitalising on this ethnographic data, we provide an analytical framework for studying complexity among the heterogeneous social category of youth agripreneurs. The aim of the paper is twofold: First, to reconcile anthropological studies that highlight the heterogeneity of African youth with demographic understandings of youth as a statistical category defined by an age bracket. Second, to advance an operational definition of youth that allows for more context-sensitive and tailored programmes. Our results suggest that while "youth" is an important category demographically, the opportunities and challenges faced by youths are often not related to age.